Pengaruh Strategi Promosi Sosial Media (Instagram) Dan Word Of Mouth Terhadap Keputusan Pembelian Kuliner Mbok taya - Rudi Hartono; Rois Arifin; Moh. Hufron (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractIn the digital era such as today's online activities have penetrated into every sector is no exception in marketing activities. Rapid technological developments have an impact on entrepreneurs, promotion of social media can be used as a sales strategy, buying and selling, and the promotion process simultaneously. This research uses explanatory research with a qualitative approach. There are four variables used in this study, namely content creation (X1), content sharing (X2), connecting (X3), word of mouth (X4) and purchasing decision structure (Y) . Data collection was obtained using online questionnaires (Google form) on mbok taya customers according to the number of Instagram followers. The sample used in this study amounted to 97 respondents, all respondents came from mbok taya customers according to the number of Instagram followers totaling 1,645 who were divided using the formula slovin get the 97 respondents. The technique used in sampling is Non-Probability analysis of the data used is descriptive analysis and multiple linear analysis, the results of this study indicate that each variable consisting of content creation (X1), content sharing (X2), connecting (X3) ), word of mouth (X4) simultaneously influences the purchase decision (Y). Based on the results of this study, mbok taya should use an online marketing strategy or social media marketing namely intsagram to strengthen purchasing decisions.keywords : social media marketing, purchase decision and word of mouth